Vascular Instability and Neurological Morbidity in Sickle Cell Disease: An Integrative Framework - Stotesbury, Hanne; Kawadler, Jamie M.; Hales, Patrick W.; Saunders, Dawn E.; Clark, Christopher A.; Kirkham, Fenella J. (Frontiers in Neurology, 2019)
Abstract It is well established that patients with sickle cell disease (SCD) are at substantial risk of neurological complications, including overt and silent stroke, diffuse structural injury, and cognitive difficulties. Yet the underlying mechanisms remain poorly understood, partly because findings have largely been considered in isolation. Here, we review mechanistic pathways for which there is accumulating evidence and propose an integrative systems-biology framework for understanding neurological risk. Drawing upon work from other vascular beds in SCD, as well as the wider stroke literature, we propose that macro-circulatory hyper-perfusion, micro-circulatory hypo-perfusion, and an exhaustion of cerebral vascular response mechanisms, together lead to a state of cerebral vascular instability. We suggest that in this state, tissue oxygen supply is fragile and easily perturbed by changes in clinical condition, with the potential for stroke and/or structural injury if metabolic demand exceeds tissue oxygenation. This framework brings together recent developments in the field, highlights outstanding questions, and offers a first step towards a linking pathophysiological explanation of neurological risk that may help inform future screening and treatment strategies.